Pengaruh Konflik Kerja Dan Beban Kerja Terhadap Kinerja Karyawan - Natalia, Kristina; Sutadi, Theodorus (EXERO : Journal of Research in Business and Economics, 2024)
This study aims to determine 1) the effect of work conflict on employee performance, 2) the effect of workload effect on employee performance, 3) the effect work conflict and workload have simultaneously on employee performance at Badan Penanggulangan Bencana Daerah Kabupaten Gunung Mas. The population in this research were all employees of Badan Penanggulangan Bencana Daerah Kabupaten Gunung Mas. The technique used in this research is satured sampling method and data collection technique by distributing questionnaires to 37 respondens. Data analysis technique in this study is multiple linear regression using the IBM SPSS 26 program. The results in this study indicate that: 1) work conflict has negative effect to employee, 2) workload has no effect on employee performance, 3) work conflict and workload have a simultaneous effect on employee performance.